The Family Series Workshop: A Community-Based Psychoeducational Intervention. (September 2015) - Llanque, Sarah M.; Enriquez, Maithe; Cheng, An-Lin; Doty, Leilani; Brotto, Marco A.; Kelly, Patricia J.; Niedens, Michelle; Caserta, Michael S.; Savage, Lynette M.
This study describes an evaluation of a community-based psychoeducational intervention, called The Family Series Workshop, for caregivers of community-dwelling persons with Alzheimer's disease or related dementias (ADRD). In a one-group pretest–posttest design, participants (n = 35) attended six weekly sessions. Caregiver stress, coping, and caregiving competence were evaluated along with demographic characteristics of participants. There was a significant improvement found for caregiving competence, and a marginally significant increase in coping with humor. Using regression analysis we also found that coping with humor, along with stress, were significant predictors of caregiving competence. These findings indicate that it is possible to increase caregiving competence utilizing a "grassroots" approach and that it is feasible to hold educational, group discussions on a plethora of challenging caregiving topics.